Luwic Dialects and Anatolian: Inheritance and Diffusion - Mariona Vernet (Col·lecció Barcino Monographica Orientalia, 2019)
This book focuses on Luwic languages, bringing together approaches from Indo-European linguistics and language reconstruction and also from other intrinsically related disciplines such as epigraphy, numismatics and archaeology, and shows very clearly how these disciplines can benefit from each other. The volume gathers together the most recent results of investigation in the field, and is the natural extension of recent work completed by a research group on Luwic dialects over a number of years. Among the thirteen contributions, fitting neatly within the Luwian and other Anatolian languages, a rich variety of subjects are covered: epigraphy, grammar, etymology, textual interpretation, and archaeological context.